1987
DOI: 10.1111/j.1600-0773.1987.tb01779.x
|View full text |Cite
|
Sign up to set email alerts
|

The Actions of Nifedipine and Nisoldipine on the Contractile Activity of Human Coronary Arteries and Human Cardiac Tissue in Vitro

Abstract: We have studied the action of nifedipine and nisoldipine on the contractile activity of human isolated coronary arteries and human isolated auricular and ventricular muscles. Nisoldipine depressed dose dependently the spontaneous rhythmic contractions displayed by the coronary artery preparations and at 1 nM abolished these contractions. Nisoldipine was twenty times more potent than nifedipine as an inhibitor of increase in tone induced by depolarization (100 mM K+). The rhythmic activity induced by serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…This property was observed in experiments on human tissues as well as animal ones (3). The coronary artery selectivity of nisol dipine was at least 10 times more pronounced than that of nifedipine (3), and the cardiodepressant effect was less po tent in human tissues (3). From such a pharmacological point of view, nisoldipine seems to be a promising drug for the treatment of ischemic heart disease.…”
mentioning
confidence: 67%
“…This property was observed in experiments on human tissues as well as animal ones (3). The coronary artery selectivity of nisol dipine was at least 10 times more pronounced than that of nifedipine (3), and the cardiodepressant effect was less po tent in human tissues (3). From such a pharmacological point of view, nisoldipine seems to be a promising drug for the treatment of ischemic heart disease.…”
mentioning
confidence: 67%
“…In this respect, nisotdipine is 100 times more vascular selective than nifedipine and is the most vascular selective of the currently available CCBs [11]. Nisoldipine, therefore, has the capacity to lower blood pressure without affecting the functioning of either the myocardium or skeletal muscle and does not produce the negative inotropic effects that occur with some other CCBs, such as nifedipine [12,13]. There is some evidence from in vitro studies, particularly using porcine artery preparations, that nisoldipine preferentially acts on the coronary rather than the peripheral vasculature, especially when the former is in a depolarized state, such as occurs during periods of ischemia [12,14,15].…”
Section: Nisoldipinementioning
confidence: 99%
“…Nisoldipine, therefore, has the capacity to lower blood pressure without affecting the functioning of either the myocardium or skeletal muscle and does not produce the negative inotropic effects that occur with some other CCBs, such as nifedipine [12,13]. There is some evidence from in vitro studies, particularly using porcine artery preparations, that nisoldipine preferentially acts on the coronary rather than the peripheral vasculature, especially when the former is in a depolarized state, such as occurs during periods of ischemia [12,14,15]. However, the results of clinical studies have not supported these observations but have suggested, instead, that nisoldipine acts equally on coronary and peripheral arteries [16][17][18].…”
Section: Nisoldipinementioning
confidence: 99%
“…Nisoldipine is a new dihydropyridine calcium antagonist with high vascular specificity [1,2]; systemic and coronary vascular resistance are substantially attenuated by nisoldipine, whereas myocardial contractility seems to be virtually unaffected by vasoactive doses of the drug [3][4][5]. However, the effects of nisoldipine on myocardial contractility in isolated systems are controversial [6].…”
Section: Keg Words Nisoldipine Coronary Vasomotility Coronary Stenmentioning
confidence: 99%